57 Serum total vitamin d levels are not associated with endothelial dysfunction, vascular stiffness or early adverse outcomes after invasive management of non-st elevation acute coronary syndrome in older patients. (5th June 2017) - Beska, Benjamin; Neely, Dermot; Datta, Harish; Gu, Sophie Zhaotao; Batty, Jonathan; Sinclair, Hannah; MacGowan, Guy; Ford, Gary; Qiu, Weiliang; Kunadian, Vijay
Abstract : Introduction: Vitamin D may be an important biomarker of cardiovascular disease. Older patients are at particularly high risk of adverse outcomes following non-ST elevation acute coronary syndrome (NSTEACS). Low vitamin D has been previously linked to endothelial dysfunction and vascular stiffness. Therefore, the higher incidence of low vitamin D in older adults may play a plausible mechanistic role in predisposing this cohort to higher risk. The association between vitamin D, endothelial function, vascular stiffness and early outcomes after invasive management of NSTEACS in older patients was evaluated. Methods: We evaluated 294 consecutive older patients (aged 65 years) with NSTEACS managed by an invasive strategy. Serum total vitamin D was measured pre-procedure by electrochemiluminescent immunoassay. Endothelial function was determined using peripheral arterial tonometry and vascular stiffness with carotid-femoral pulse wave velocity (PWV), both within 24 hours post-procedure. Major Adverse Cardiovascular Events (MACE) were defined as 30 day composite of all-cause mortality, acute coronary syndrome, unplanned repeat revascularisation, significant bleeding, stroke or transient ischaemic attack. Multivariate linear and logistic regressions were performed controlling for age, sex, serum triglycerides, hypertension, diabetes and smoking status. Results: Mean age was 80.5±4.8 years (61.9% male). Median vitamin D level was 29.5 nmol/L [IQR 16.0–53.0 nmol/L] and was split into quartiles for analysis: Q1 (16.0 nmol/L, n=72), Q2 (17.0–29.5 nmol/L, n=75), Q3 (30.0–53.0 nmol/L, n=72) and Q4 (54.0 nmol/L, n=72). There was no difference in endothelial function (p=0.337) or PWV (p=0.633) between the vitamin D quartiles. There was no adjusted linear relationship between vitamin D and PWV (p=0.410) or endothelial function (p=0.490). MACE incidence did not differ between quartiles (Q1 2.7%; Q2 0%; Q3 5.3%; Q4 5.6%; p=0.210) and adjusted for confounders, did not significantly predict MACE (p=0.083). Conclusion: In this high-risk older cohort, pre-procedural serum total vitamin D level is not associated with endothelial dysfunction or vascular stiffness and is not predictive of short-term outcomes after invasive management of NSTEACS.